The Antioxidant and DPP-4 Inhibitory Potential of n-Hexane, Ethyl Acetate, and Aqueous Fractions From Potential Avicennia marina Fruit - Retno Utomo; Kyky Herlyanti; Dwi Hadi Setya Palupi; M. Noufal Hafidh (Media Farmasi Indonesia, 2026)
Avicennia marina is one type of mangrove plant fruit that can be utilized for medical purposes through natural ingredients,one of which is the treatment of diabetes mellitus. Avicennia marina contains secondarynmetabolites such as flavonoids, alkaloids, tannins, saponins, and terpenoids that have antioxidant and antidiabetic activities. The aim of this study is to determine the potential of n-hexane, ethyl acetate and water fractions of Avicennia marina fruit as antioxidants using DPPH method and their antidiabetic activity through the inhibition of the enzyme dipeptidyl peptidase-IV (DPP-IV) in vitro. The sample used fruit of avicennia marina, which was extracted using maceration methode with 96% ethanol for 3x24 hours. The obtained extract was fractinationated stepwise using n-hexane, ethyl acetate, and water as solvents. The test results on the n-hexane fraction showed antioxidant activity with an IC₅₀ value of 77.744 µg/mL and a DPP-4 inhibition percentage of 18.07%; the ethyl acetate fraction had an IC₅₀ value of 45.2738 µg/mL and a DPP-4 inhibition of 64.04%; while the water fraction had an IC₅₀ of 95.6466 µg/mL with a DPP-4 inhibition percentage of 43.99%. Based on these results, the ethyl acetate fraction of the api-api fruit shows the highest potential both as an antioxidant and as a DPP-4 enzyme inhibitor.